2018
DOI: 10.1002/jsde.12161
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Comparison on Foam Behavior in the Presence of Light Oil and Heavy Oil

Abstract: Crude oil properties significantly affect foam behavior that is important to foam application in enhanced oil recovery. This study focused on the comparison on foam behavior in the presence of light oil and heavy oil. Foamability and foam stability, the bubble size, and the film thickness as well as the configuration of oil drops were fully investigated. Final results indicated that both the heavy oil and light oil increased the foamability of sodium dodecyl sulfate but decreased that of the amphoteric surfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…4,5 It is indicated that the foam is an ideal hightemperature profile control and flooding agent, and thus, foam is widely used in steam flooding for improving heavy oil recovery. 6,7 The experimental results by Bagheri and Clark showed that foam-assisted steam flooding could achieve good results, which verified the application prospect of foam-assisted steam flooding in the Canadian thermal recovery project being developed in northwest Alberta. 8 Wang et al carried out physical simulation experiments to prove that the flue gas foam-assisted steam flooding technology had a good ability to improve the recovery of steam flooding.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…4,5 It is indicated that the foam is an ideal hightemperature profile control and flooding agent, and thus, foam is widely used in steam flooding for improving heavy oil recovery. 6,7 The experimental results by Bagheri and Clark showed that foam-assisted steam flooding could achieve good results, which verified the application prospect of foam-assisted steam flooding in the Canadian thermal recovery project being developed in northwest Alberta. 8 Wang et al carried out physical simulation experiments to prove that the flue gas foam-assisted steam flooding technology had a good ability to improve the recovery of steam flooding.…”
Section: Introductionmentioning
confidence: 74%
“…Foam-assisted steam flooding is an effective technology to improve the sweep efficiency of steam flooding by inhibiting the steam channeling and gravity override, thus increasing the oil recovery of steam flooding. The high-temperature foam agent can not only inhibit the steam overriding but also reduce the steam mobility. Besides, the foam also has the selective blocking characteristics, which can block the big pores rather than the small pores and block the water layers rather than the oil layers. , It is indicated that the foam is an ideal high-temperature profile control and flooding agent, and thus, foam is widely used in steam flooding for improving heavy oil recovery. , The experimental results by Bagheri and Clark showed that foam-assisted steam flooding could achieve good results, which verified the application prospect of foam-assisted steam flooding in the Canadian thermal recovery project being developed in northwest Alberta . Wang et al carried out physical simulation experiments to prove that the flue gas foam-assisted steam flooding technology had a good ability to improve the recovery of steam flooding. , …”
Section: Introductionmentioning
confidence: 99%
“…Crude oil has favorable and unfavorable effects on foaming capacity. , Pang and Rohani have extensively researched how oil and foam interact. Research has shown that when foam interacts with crude oil, it becomes more stable.…”
Section: Resultsmentioning
confidence: 99%
“…The driving force of draining is the gravity force and the pressure difference between the plateau border and the planar film, and the resistance is the viscous force of liquid. Generally, the oil enters the lamella to form emulsion, and the larger the oil viscosity, the larger the particle size of the emulsion formed and the greater the resistance to drainage [25]. From Table 1, the viscosity of the oil is: heavy oil > light oil The influence of oil on foam stability originates from the interaction between lipophilic groups and active molecules [24].…”
Section: Foaming Ability and Stabilitymentioning
confidence: 99%